Achievement of Graduate Competency Standards in Malay Hantaran Training at PKBM Insan Cendikia - Adelia Razis Putri; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Community Learning Centers are non-formal education institutions established by communities to provide educational services, skills training, and empowerment programs aimed at improving the quality of life. This study aims to analyze the achievement of graduate competency standards in the Malay Hantaran-Making Skills Training Program organized by Pusat Kegiatan Belajar Masyarakat (PKBM) Insan Cendikia. A qualitative approach was employed using data triangulation through semi-structured interviews, participatory observation, and document analysis. Research subjects included program managers and tutors. Results indicate that the program successfully achieved most key performance indicators (KPIs): 90% participant attendance rate, 60% competency test pass rate through the Competency Testing Center (TUK), 80% market-quality products, sustained skill application, and 40% of participants gaining supplementary income. These findings suggest that PKBM Insan Cendikia has effectively delivered a non-formal education program that transfers locally-based cultural skills while empowering community economic outcomes. Recommendations include improving financial documentation systems, intensive remedial programs, and digital entrepreneurship incubation development.